131k views
3 votes
If f(x) = x + 7 and g(x) = Square root X-3,
what is (fºg)(4)?

If f(x) = x + 7 and g(x) = Square root X-3, what is (fºg)(4)?-example-1
User Weegee
by
4.7k points

2 Answers

3 votes

Answer:

x =
√(4) = ±2

Explanation:


√(-x+7+x-3) =
√(4)

User SunLiWei
by
5.0k points
5 votes

Answer:

Explanation:

If f(x) = x + 7 and g(x) = Square root X-3, what is (fºg)(4)?-example-1
User Samuel Clay
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.